2014
DOI: 10.17229/jdit.2014-0712-002
|View full text |Cite
|
Sign up to set email alerts
|

An in vivo Positron Emission Tomography Study of Adenosine 2A Receptor Occupancy by Preladenant using 11C-SCH442416 in Healthy Subjects

Abstract: 21novel non-dopaminergic, high-affinity, and highly selective A 2A receptor antagonist being investigated for the management of Parkinson's disease. Methods:This was an open-label, single-center, and pharmacokinetic-pharmacodynamic study performed in 18 healthy subjects. All subjects received an intravenous injection of the radiotracer 11 C-SCH442416. Thirteen subjects received a single dose of preladenant 10, 50 or 200 mg orally at 1, 6 or 12 hrs prior to radiotracer injection.Results: A blockade of >80% was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Two later studies have shown very different specific binding potentials in the putamen when using the cerebellum as a reference region for the estimation of specific radioligand binding. Grachev et al [ 148 ] reported the average binding potential (BP ND ) of five healthy subjects in the putamen as 2.47 ± 0.84, whereas Ramlackhansingh et al [ 15 ] reported the average BP ND of six healthy controls (control group in a PD study) to be as low as 0.99 ± 0.21. The intersubject variability was, however, fairly large in the aforementioned study (BP ND 1.12–3.82 in the putamen) [ 148 ].…”
Section: A 2a Receptor-binding Radioligands In mentioning
confidence: 99%
See 1 more Smart Citation
“…Two later studies have shown very different specific binding potentials in the putamen when using the cerebellum as a reference region for the estimation of specific radioligand binding. Grachev et al [ 148 ] reported the average binding potential (BP ND ) of five healthy subjects in the putamen as 2.47 ± 0.84, whereas Ramlackhansingh et al [ 15 ] reported the average BP ND of six healthy controls (control group in a PD study) to be as low as 0.99 ± 0.21. The intersubject variability was, however, fairly large in the aforementioned study (BP ND 1.12–3.82 in the putamen) [ 148 ].…”
Section: A 2a Receptor-binding Radioligands In mentioning
confidence: 99%
“…Grachev et al [ 148 ] reported the average binding potential (BP ND ) of five healthy subjects in the putamen as 2.47 ± 0.84, whereas Ramlackhansingh et al [ 15 ] reported the average BP ND of six healthy controls (control group in a PD study) to be as low as 0.99 ± 0.21. The intersubject variability was, however, fairly large in the aforementioned study (BP ND 1.12–3.82 in the putamen) [ 148 ]. In both studies spectral analysis with metabolite corrected arterial plasma input and cerebellum as a reference region were used for the quantification of specific radiotracer binding.…”
Section: A 2a Receptor-binding Radioligands In mentioning
confidence: 99%